PENGARUH PANDEMI COVID 19 PADA TIMBULAN DAN KOMPOSISI SAMPAH RUMAH TANGGA DI KELURAHAN PENJARINGAN SARI KECAMATAN RUNGKUT KOTA SURABAYA - AhmadYoga Prasetya; Naniek Ratni J.A.R (EnviroUS, 2021)
Penjaringan Sari is one of the urban villages in Surabaya. Based on the explanation from the Surabaya City Health and Garden Office, the most waste generation comes from household waste (residential areas) which reaches 79.19% of the total waste generation. Currently in Surabaya is facing an outbreak of an easily transmitted disease called Covid 19. This has resulted in reduced activities outside the home which automatically increase the number of activities at home. Waste generation in 2017 averaged 0.35 kg / person per day. This research will be compared with previous research to find out how household waste is generated during the Covid 19 pandemic and the composition of household waste in residential areas in Penjaringan Sari Village, Surabaya City. Household waste generation in residential areas, flats, and villages in Penjaringan Sari village during the Covid 19 pandemic amounted to 0.361 kg / person per day, 0.345 kg / person per day, and 0.530 kg / person per day. Which means an increase of 0.09 kg / person per day for residential areas, 0.063 kg / person per day for the apartment area, and 0.044 kg / person per day for the village area. The composition of household waste in the Penjaringan sari village is dominated by compostable waste and the composition of waste that experienced the largest increase was plastic, cloth, glass and metal waste.